Decolorization of industrial dyes by a Brazilian strain of Pleurotus pulmonarius producing laccase as the sole phenol-oxidizing enzyme - Zilly, A; Souza, C G M; Barbosa-Tessmann, I P; Peralta, R M (Folia microbiologica, 2002)
The ability of a Brazilian strain of Pleurotus pulmonarius to decolorize structurally different synthetic dyes (including azo, triphenylmethane, heterocyclic and polymeric dyes) was investigated in solid and submerged cultures. Both were able to decolorize completely or partially 8 of 10 dyes (Amido Black, Congo Red, Trypan Blue, Methyl Green, Remazol Brilliant Blue R, Methyl Violet, Ethyl Violet, Brilliant Cresyl Blue). No decolorization of Methylene Blue and Poly R 478 was observed. Of the four phenol-oxidizing enzymes tested in culture filtrates (lignin peroxidase, manganese peroxidase, aryl alcohol oxidase, laccase), P. pulmonarius produced only laccase. Both laccase activity and dye decolorization were related to glucose and ammonium starvation or to induction by ferulic acid. The decolorization in vivo was tested using three dyes--Remazol Brilliant Blue R, Trypan Blue and Methyl Green. All of them were completely decolorized by crude extracellular extracts. Decolorization and laccase activity were equally affected by pH and temperature. Laccase can thus be considered to be the major enzyme involved in the ability of P. pulmonarius to decolorize industrial dyes.
Keywords: Laccase; průmyslová mikrobiologie; barvicí látky; tyrosinasa; Fermentation; lakasa; Monophenol Monooxygenase; Brazil; Oxidoreductases; Coloring Agents; Brazílie; Industrial Microbiology; Pleurotus; fermentace; oxidoreduktasy